THE PROFILE OF CREATIVE THINKING PROCESS: PROSPECTIVE MATHEMATICS TEACHERS - Gunawan Gunawan; Ferry Ferdianto; Fauzi Mulyatna; Reni Untarti (Jurnal Eduscience)
Purpose The creative thinking process is one of the important components of creativity. The profile of the creative thinking process of prospective mathematics teachers based on the level of creativity is explained in this study.